Rethinking Materiality, Memory and Identity - Tracy Ireland; Jane Lydon (Public History Review, 2016)
This introductory article  considers and questions exactly how materials and people constitute social worlds and relationships which sustain identity and memory and, in turn, the social and political structures or norms that these attachments invest in, stabilise and maintain.